2021
DOI: 10.1136/tsaco-2020-000642
|View full text |Cite
|
Sign up to set email alerts
|

Decreased adult trauma admission volumes and changing injury patterns during the COVID-19 pandemic at 85 trauma centers in a multistate healthcare system

Abstract: BackgroundReports indicate social distancing guidelines and other effects of the COVID-19 pandemic impacted trauma patient volumes and injury patterns. This report is the first analysis of a large trauma network describing the extent of these impacts. The objective of this study was to describe the effects of the COVID-19 pandemic on patient volumes, demographics, injury characteristics, and outcomes.MethodsFor this descriptive, multicenter study from a large, multistate hospital network, data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 15 publications
4
51
0
Order By: Relevance
“…In our study, trauma surgery covered almost 30% of the whole surgical volumes. We observed a significant decrease in trauma surgery, in line with several reports from other countries and from the adult counterpart [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. We agree with some authors that this decline in emergency referrals was more related to the combination of seasonal trends of pediatric trauma and concomitant restriction of sportive and outdoor recreational activities during the lockdown periods, rather than the effect of contraction or reallocation of healthcare resources [ 10 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, trauma surgery covered almost 30% of the whole surgical volumes. We observed a significant decrease in trauma surgery, in line with several reports from other countries and from the adult counterpart [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. We agree with some authors that this decline in emergency referrals was more related to the combination of seasonal trends of pediatric trauma and concomitant restriction of sportive and outdoor recreational activities during the lockdown periods, rather than the effect of contraction or reallocation of healthcare resources [ 10 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…[ 18 , 19 , 20 , 21 ]. Another and more worrying explanation could be that, while the overall volumes of trauma patients decreased, the injury pattern changed, as reported in recent studies concerning adult trauma [ 13 , 14 ], thus requiring hospitalization more frequently. Lockdown- and quarantine-related measures, such as school closings and social isolation, could have increased domestic violence, child abuse or neglect, and self-harm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the leading reasons for emergency admissions is traumatic injuries. In the literature, many studies reported that there was also a decrease in admissions to the emergency departments attributable to trauma during the COVID-19 pandemic [6][7][8][9]. The vast majority of these studies were associated with orthopedic injuries and did not contain abdominal trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injury patterns are linked to population behaviours, and COVID-19 Pandemic has changed the population behaviours significantly [8]. Whilst the patient demographics remain similar, there has been a reduction in the volume of traumatic adult and paediatric injuries [8][9][10]. The severity of these injuries has gone up on average, and a higher proportion of patients requiring surgery has been described [8,10].…”
Section: Introductionmentioning
confidence: 99%